2013
DOI: 10.1002/ep.11861
|View full text |Cite
|
Sign up to set email alerts
|

Settling and bioflocculation of two species of algae used in wastewater treatment and algae biomass production

Abstract: The settling and bioflocculation of two strains of algae were investigated in the laboratory to provide insights to help improve algae settling in large-scale, algae-based wastewater treatment systems with simultaneous algae biofuel production. Energy-efficient algae harvesting methods are needed for cost-competitive production of biofuels from algae. The use of bacterially derived exudates (bioflocculation) is promising, but its use in high-rate algae pond (HRAP) wastewater systems has not yielded consistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 39 publications
(84 reference statements)
1
26
0
Order By: Relevance
“…As it was referred in the 'Surface physicochemical properties' section, when absolute value of zeta potential is high, repulsive forces prevail over van der Waals forces, and hence, particles/cells are stable in the dispersed form. Similar removal percentages have been reported by Salim et al [40] and Manheim and Nelson [56] when harvesting microalgae through bioflocculation. Higher removal percentages can be achieved using chemical coagulants/flocculants.…”
Section: Sedimentation Kineticssupporting
confidence: 73%
“…As it was referred in the 'Surface physicochemical properties' section, when absolute value of zeta potential is high, repulsive forces prevail over van der Waals forces, and hence, particles/cells are stable in the dispersed form. Similar removal percentages have been reported by Salim et al [40] and Manheim and Nelson [56] when harvesting microalgae through bioflocculation. Higher removal percentages can be achieved using chemical coagulants/flocculants.…”
Section: Sedimentation Kineticssupporting
confidence: 73%
“…Similar results have been reported by Manheim et al . 18 and Oh et al . 25 , who found that bioflocculation by bacteria and their exudates could improve the microalgae settling.…”
Section: Resultsmentioning
confidence: 93%
“…After algae are cultivated, the biomass typically needs to be harvested and dewatered to a more concentrated algal slurry as the next processing step. There are different approaches for accomplishing this concentration which include flocculation, centrifugation, and filtration . The wet slurry is then typically either dried or subjected as wet biomass to a solvent extraction step or some sort of thermochemical conversion step to produce a biofuel intermediate .…”
Section: Conversion Of Algae To Biocrude/intermediatesmentioning
confidence: 99%
“…After algae are cultivated, the biomass typically needs to be harvested and dewatered to a more concentrated algal slurry as the next processing step. There are different approaches for accomplishing this concentration which include flocculation, centrifugation, and filtration [28][29][30].…”
Section: Conversion Of Algae To Biocrude=intermediatesmentioning
confidence: 99%